2021
DOI: 10.1126/sciimmunol.abh1516
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal expansion of TCR Vβ 21.3+CD4+and CD8+T cells is a hallmark of multisystem inflammatory syndrome in children

Abstract: Multiple Inflammatory Syndrome in Children (MIS-C) is a delayed and severe complication of SARS-CoV-2 infection that strikes previously healthy children. As MIS-C combines clinical features of Kawasaki disease and Toxic Shock Syndrome (TSS), we aimed to compare the immunological profile of pediatric patients with these different conditions. We analyzed blood cytokine expression, and the T cell repertoire and phenotype in 36 MIS-C cases, which were compared to 16 KD, 58 TSS, and 42 COVID-19 cases. We observed a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
5
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 54 publications
6
84
5
3
Order By: Relevance
“…When analyzing the dataset in individual patient samples, we found that approximately half of the MIS-C patients contributed to most TRBV11-2 + cells (Fig. 6 F), reminiscent of proportions described in previous studies (Moreews et al, 2021;Porritt et al, 2021;Ramaswamy et al, 2021). Nonetheless, in all MIS-C samples, significantly high proportions of the activated or proliferative cells (clusters 14 and 15) consisted of TRBV11-2expressing cells, supporting a similar disease course in all patients (Fig.…”
Section: Mis-c and Severe Covid-19 Have Similar Numbers Of Circulating Ifnγ + Sars-cov-2-specific T Cellssupporting
confidence: 79%
“…When analyzing the dataset in individual patient samples, we found that approximately half of the MIS-C patients contributed to most TRBV11-2 + cells (Fig. 6 F), reminiscent of proportions described in previous studies (Moreews et al, 2021;Porritt et al, 2021;Ramaswamy et al, 2021). Nonetheless, in all MIS-C samples, significantly high proportions of the activated or proliferative cells (clusters 14 and 15) consisted of TRBV11-2expressing cells, supporting a similar disease course in all patients (Fig.…”
Section: Mis-c and Severe Covid-19 Have Similar Numbers Of Circulating Ifnγ + Sars-cov-2-specific T Cellssupporting
confidence: 79%
“…It has been suggested that in MIS‐C patients, the T‐cell response is compromised and that a specific oligoclonal expansion of V beta 21.3 T cells defines the T‐cell repertoire [ 17 ]. Our data on the SARS‐CoV‐2‐specific T‐cell response neither suggest a defect in antiviral‐specific T cells nor were there differences in the virus‐specific T‐cell responses in the children with MIS‐C compared to convalescent controls following SARS‐CoV‐2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Second, previous studies have shown that OS is involved in the acute stage of KD, caused by an overproduction of ROS for activated inflammatory cells ( 60 ). Although MIS-C has clinical similarities and cytokine profiles comparable to KD and TSS, recent studies suggest that there are differences in the type of activated cells during the immune response, observing a specific expansion of activated T lymphocytes that express the Vβ21.3 T cell receptor β chain variable region in CD4 and CD8 cells, something that differs in KD, TSS patients or SARS-COV-2 ( 61 ). In addition, the antibody response in MIS-C compared to adults with severe COVID-19 presents important differences, for example, a study showed that patients with MIS-C produced predominantly specific IgG antibodies (Abs) for the S protein but not for the N protein and in addition to a reduced neutralizing activity, while adult patients with COVID-19 presented Abs anti-S IgG, IgM and IgA, as well as Abs anti-N IgG, these results suggested that the immunological profile in MIS-C presents certain differential characteristics of COVID-19 in adults ( 62 ).…”
Section: Oxidative Stress and Covid-19mentioning
confidence: 99%